2002
DOI: 10.1075/sll.5.1.04mck
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting into International Sign Pidgin

Abstract: sign has been used in interpreting for almost twenty years, no empirical research has described the unique phenomenon of international sign interpreting. This study analyzes data samples of interpretation from spoken English into International Sign Pidgin at international conferences and sports meetings. Predominant linguistic characteristics of the target language output are identified in the first section, while the second section describes strategies that international interpreters use to manage the task of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 2 publications
0
24
0
4
Order By: Relevance
“…Thus, the signed modality alone is not enough to presume that the same processes, for example, for creating intersubjectivity, are at work, and this is a matter of empirical research. On the other hand, International Sign (IS), being used by adult signers as an international lingua franca (McKee & Napier, ; Rosenstock, ), is likely to have parallels with cross‐signing in its development because the sociolinguistic context is very similar, and cross‐signing is claimed to be “a window into the past of the development of IS” in Zeshan (, p. 254).Within cross‐signing, the extent and patterns of individual differences between signers as to the resources and strategies used for repair need to be subject to future research. Moreover, it is also acknowledged here that OIR sequences can have more complex patterns, for example, repeated repair attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the signed modality alone is not enough to presume that the same processes, for example, for creating intersubjectivity, are at work, and this is a matter of empirical research. On the other hand, International Sign (IS), being used by adult signers as an international lingua franca (McKee & Napier, ; Rosenstock, ), is likely to have parallels with cross‐signing in its development because the sociolinguistic context is very similar, and cross‐signing is claimed to be “a window into the past of the development of IS” in Zeshan (, p. 254).Within cross‐signing, the extent and patterns of individual differences between signers as to the resources and strategies used for repair need to be subject to future research. Moreover, it is also acknowledged here that OIR sequences can have more complex patterns, for example, repeated repair attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Such signed interactions, where communication emerges ad hoc between individuals without a shared language, have been designated “cross‐signing” (Bradford, Sagara, & Zeshan, ; Zeshan, ). Importantly, cross‐signing is distinct from International Sign, which can be considered a semi‐conventionalized pidgin and has developed over a substantial time period as the main form of communication at international gatherings of Deaf people such as the congresses and events hosted by transnational organizations, including the World Federation of the Deaf or the European Union of the Deaf (Allsop, Woll, & Brauti, ; McKee & Napier, ; Supalla & Webb, ).…”
Section: Introductionmentioning
confidence: 99%
“…IS has developed as a contact variety between deaf signers from different countries and is used widely in international gatherings of deaf people such as the conferences and congresses of the World Federation of the Deaf (cf. McKee and Napier 2002). IS has the sociolinguistic characteristics of a pidgin and has at times been recognised as such, though its linguistic status is a contested issue (Supalla and Webb 1995).…”
Section: "Making Meaning"mentioning
confidence: 99%
“…MS JD and MI IND had also occasionally encountered deaf foreigners in their home countries, but 1 IS has the sociolinguistic characteristics of a pidgin, e.g., it arose from language contact and has no native users, but it has additional particularities unlike those found in spoken language pidgins which are based on its visual modality (see Supalla and Webb 1995;McKee and Napier 2002). 2 In fact, they have been able to acquire new skills and to use those skills in the context of their countries of origin.…”
mentioning
confidence: 99%
“…Studies on international communication in sign language and interpreting in international meetings and events have shown that grammatical features of IS are highly complex and make use of the same structures that natural sign languages share (e.g. Bergmann 1990, Woll 1990, Allsop, Woll & Brauti 1994, Webb & Supalla 1994, Supalla and Webb 1995, Moody 2002, Locker McKee and Napier 2002, Rosenstock 2004, 2005. Still some researchers have argued that more research is needed especially on face-to-face communication and describing IS in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%